A life management guide for developing the financial literacy of secondary school students - Bako, Tamas (Національний технічний університет "Харківський політехнічний інститут", 2025)
The article considers conceptual approaches to the development of financial literacy of secondary school students and presents the model of the “Life Management Guide” as a tool for the formation of practical financial competencies. Based on the analysis of international studies by the OECD, PISA and the works of leading authors, the importance of combining knowledge, skills, financial behavior and self-efficacy in adolescence is substantiated. It is shown that the level of financial literacy of young people largely depends on the family environment and the quality of national financial education strategies. The article analyzes international practices of early financial education and outlines key pedagogical principles necessary for building an effective educational manual aimed at preparing students for real financial decisions and independent living. Additionally, the need for systematic integration of financial education into the content of curricula at different levels is emphasized, which ensures consistency and continuity of competence development. The proposed approach is aimed at forming in schoolchildren the ability to make responsible economic decisions and critically evaluate their own financial behavior. The developed manual stimulates the development of life skills that support financial autonomy, and also contributes to the formation of motivation for long-term planning. Special attention is paid to active learning methods that allow students to apply financial knowledge in real and close to real-life situations. У статті розглянуто концептуальні підходи до розвитку фінансової грамотності учнів середньої школи та представлено модель «Гід з управління життям» як інструмента формування практичних фінансових компетентностей. На основі аналізу міжнародних досліджень ОЕСР, PISA та праць провідних авторів обґрунтовується важливість поєднання знань, навичок, фінансової поведінки та самоефективності у підлітковому віці. Показано, що рівень фінансової грамотності молоді значною мірою залежить від сімейного середовища та якості національних стратегій фінансової освіти. У статті проаналізовано міжнародні практики ранньої фінансової освіти та окреслено ключові педагогічні принципи, необхідні для побудови ефективного освітнього посібника, спрямованого на підготовку учнів до реальних фінансових рішень та самостійного життя. Додатково підкреслено необхідність системної інтеграції фінансової освіти у зміст навчальних програм різних рівнів, що забезпечує послідовність та безперервність розвитку компетентностей. Запропонований підхід спрямований на формування у школярів уміння приймати відповідальні економічні рішення та критично оцінювати власну фінансову поведінку. Розроблений посібник стимулює розвиток життєвих навичок, що підтримують фінансову автономію, а також сприяє формуванню мотивації до довгострокового планування. Окрему увагу приділено методам активного навчання, які дозволяють учням застосовувати фінансові знання в реальних та наближених до реальних життєвих ситуаціях.
Гід з управління життям для розвитку фінансової грамотності учнів середньої школи
Keywords: financial literacy; high school students; financial education; financial management; financial education strategy; budgeting; international practices; фінансова грамотність; учні середньої школи; фінансова освіта; управління фінансами; стратегія фінансової освіти; бюджетування; міжнародні практики